Selectfluor-Mediated Tandem Cyclization of Enaminones for the Synthesis of 3-Fluorochromones - Kandula, Venu; Thota, Pradeep Kumar; Mallesham, Poosa; Raghavulu, K.; Chatterjee, Anindita; Yennam, Satyanarayana; Behera, Manoranjan (Synlett, 2019)
An efficient synthesis of various 3-fluorochromones (3-fluoro-4H-chromene-4-ones) from enamino ketones by using Selectfluor is described. The key step in the synthesis involves tandem fluorination and cyclization to form 3-fluorochromones in good yields. The significant features of this method include simple operational procedures, a high purity of the product, and excellent regioselectivity.
Keywords: fluorochromones; enamino ketones; fluorination; Selectfluor